Extending the Shamir threshold secret sharing scheme for sharing simultanneously several secrets - Hoàng, Vũ Huy; Thuần, Hồ (Journal of Computer Science and Cybernetics, 2012)
Secret sharing schemes are very important techniques for the key management in cryptography and for the distributed computation. In 1979, Shamir [6] proposed a threshold secret sharing scheme in which one secret is divided into w pieces (shares) and are delivered to w users such that only groups of t or more users (t < w) could cooperately reconstruct the secret. In this paper, by extending the method of Shamir, we present a scheme for sharing simultaneously several secrets which is more effective in using memory space and computation time w.r.t the <span lang="ZH-CN" style="color: black; font-family: "Times New Roman","serif"; font-size: 12pt; mso-ansi-language: ZH-CN; mso-bidi-font-family: "Microsoft Sans Serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-language: VI; mso-bidi-language: AR-SA;">consecutive<span lang="ZH-CN" style="color: black; font-family: "Times New Roman","serif"; font-size: 12pt; mso-ansi-language: VI; mso-bidi-font-family: "Microsoft Sans Serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-language: VI; mso-bidi-language: AR-SA;"> application of several times the Shamir’s original scheme for each secret to be shared.